Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4103/2231-0770.179554
|View full text |Cite
|
Sign up to set email alerts
|

The role of war trauma survivors in managing their own mental conditions, Syria civil war as an example

Abstract: War trauma leads to a wide range of psychological consequences and disorders that can be quite disabling to individuals and their families. At times of war, existing resources become strained to cope with all demands of trauma sufferers. The survivors’ role of managing their own mental conditions becomes highly important and relevant as a way of reducing the resulted suffering. Unfortunately, this role is often ignored or trivialized by all concerned. The self-efficacy and resilience of people are the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The role of refugee survivors in self-managing their psychological well-being needs to be better understood and encouraged. This gives further support that an integrated approach is required for refugees in these settings [29].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The role of refugee survivors in self-managing their psychological well-being needs to be better understood and encouraged. This gives further support that an integrated approach is required for refugees in these settings [29].…”
Section: Discussionmentioning
confidence: 63%
“…Refugees valued the opportunity to narrate their experiences in the current research and found this validating both in terms of their health and as an important form of informal justice recovery. Greater involvement of CSOs and local NGOs in supporting refugees' own solutions would be a starting point for this process [29]. The research emphasises the benefits of the importance of listening, validating and documenting refugee experiences on a regular basis in order to provide more culturally sensitive, gendered and effective services that more closely meet their specific needs [41].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More positive beliefs about the sense of internal control have been associated with coping strategies, which are generally considered more adaptive such as positive reinterpretation, seeking social support and actively trying to tackle the problem [47]. Traumatized refugees who experienced war, forced migration or violence perceive absence of control over their lives-this can contribute to poor health as diet, exercise and medical treatment are neglected [48].…”
Section: Discussionmentioning
confidence: 99%
“…Children living in regions of war are exposed to numerous types of traumatic events that have a significant impact on their psychological and physical wellbeing (1). Various psychological responses are observed in children such as increased clinginess, mutism, attachment difficulties, anxiety, behavioral problems, sleep disturbances, bed wetting, and PTSD (2). PTSD is a psychiatric disorder that can occur following the experiencing or witnessing life-threatening events such as military combat.…”
Section: Introductionmentioning
confidence: 99%